2015
DOI: 10.1017/s1473550414000731
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effects of the outer space environment on dormant forms of microorganisms, fungi and plants in the ‘Expose-R’ experiment

Abstract: Investigations of the effects of solar radiation combined with the spaceflight factors on biological objects were performed in the «EXPOSE-R» experiment on the outer surface of ISS. After more than 1 year of outer space exposure, the spores of microorganisms and fungi, as well as two species of plant seeds were analysed for viability and the set of biological properties. The experiment provided evidence that not only bacterial and fungal spores but also dormant forms of plants had the capability to survive a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…1C), indicating that accumulated damage could not be overcome through repair and redundancy. In addition, Arabidopsis seeds were completely killed in a separate experiment on EXPOSE-R (Novikova et al, 2015). A survival endpoint was thus reached in Arabidopsis, and the results from EXPOSE-E, where exposure was lower and better survival occurred, were corroborated and extended.…”
Section: Discussionmentioning
confidence: 99%
“…1C), indicating that accumulated damage could not be overcome through repair and redundancy. In addition, Arabidopsis seeds were completely killed in a separate experiment on EXPOSE-R (Novikova et al, 2015). A survival endpoint was thus reached in Arabidopsis, and the results from EXPOSE-E, where exposure was lower and better survival occurred, were corroborated and extended.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of spaceexploration missions, bacterial and fungal spores may act as an effective vehicle for the transfer of life from Earth to extraterrestrial locations in a dormant yet viable state (Rummel et al, 2014;Gibney, 2016;Nagler et al, 2016). Spores of aspergilli and closely related fungi are highly stress resistant (van Leeuwen et al, 2013;Rangel et al, 2015;Wyatt et al, 2015b) and can remain viable after exposure to space at least 22 months, as demonstrated by the EXPOSE-R experiment performed on the outer surface of the International Space Station (Novikova et al, 2015), though may potentially do so for decades. In the current study, production of aerial hyphae and/or conidiophores and lawns of (pigmented) spores were recorded on 10 out of the 18 germination media (Figs 1 and S4).…”
Section: Production Of Mycelium and Sporulation: The Culmination Of Dmentioning
confidence: 99%
“…Also angiosperms have been tested for irradiation resistance under space conditions: 23% of Arabidopsis thaliana and Nicotina tabacum seeds developed viable plants after space exposure in LEO for 558 days, receiving irradiation doses of 7.4 · 10 5 kJ$m -2 UV 110-400nm (Tepfer et al, 2012). However, when A. thaliana seeds were exposed to higher doses of 10.3 · 10 5 kJ$m -2 UV 110-400nm for 682 days at the ISS EXPOSE-R platform, seeds hardly survived (Novikova et al, 2015;Tepfer and Leach, 2017). YIELD from before the investigation was used as a factor and compared with Yield values at the end of the experiment.…”
Section: Discussionmentioning
confidence: 99%